1948 a history of the first Arab-Israeli war - Morris, Benny 1948- (Yale University Press, 2008)
This history of the foundational war in the Arab-Israeli conflict is groundbreaking, objective, and deeply revisionist. Besides the military account, it also focuses on the war's political dimensions. Historian Morris probes the motives and aims of the protagonists on the basis of newly opened Israeli and Western documentation. The Arab side--where the archives are still closed--is illuminated with the help of intelligence and diplomatic materials. Morris stresses the jihadi character of the two-stage Arab assault on the Jewish community in Palestine. He examines the dialectic between the war's military and political developments and highlights the military impetus in the creation of the Palestinian refugee problem. He looks both at high politics and general staff decision-making and at the nitty-gritty of combat in the battles that resulted in the emergence of the State of Israel and the humiliation of the Arab world--a humiliation that underlies the continued Arab antagonism toward Israel.